RASIONALISASI TINDAKAN SOSIAL MASYARAKAT SUKU SASAK TERHADAP TRADISI PERANG TOPAT (Studi Kasus Masyarakat Islam Sasak Lombok Barat) - Suparman Jayadi (Program Studi Sosiologi Agama Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2017)
Traditions Perang Topat in Lingsar Village has done tens of years. The ritual of progress remains a tradition by the Sasak community consisted of religious understanding difference, namely the Sasak Muslim and Hindus performed simultaneously at one time and the same place. In this study discusses how the process of implementation of a tradition of Perang Topat, then the history of the tradition of Perang Topat and also forms the rationalization of social action. Research using the instrumental rationalization and value theory of Max Weber’s approach to qualitative case studies in the tradition of Perang Topat. The results of this study indicate that on the rationalization of the social action community Sasak is two Shapes in the implementation of a tradition of Perang Topat are: social value and sacred value. The form of social value is first, tying religious solidarity. Second, create value tolerance and bring peace. Third the form of local wisdom in Sasak. While the shape of the sacred is the first, this form of gratitude to the ancestral spirits are spirits of ancestors or the death (God Almighty) upon which it was holy water in Llingsar and Kemaliq. Second, a form of communication to the ancestral spirits or spirits of the ancestors of the death (God).Keywords: Rationalization, Social Action, Community Sasak, and Topat War Tradition.